Global Regulation of Flexible Joint Robots With Input Saturation by Nonlinear I-PID-Type Control - Moyron, Jeronimo; Moreno-Valenzuela, Javier; Sandoval, Jesus (IEEE transactions on control systems technology, 2024)
This brief addresses the global regulation of torque-driven flexible joint robots with input constraints. It is reported a nonlinear control scheme with bounded actions that guarantees global asymptotic stability despite input saturation, matched and unmatched disturbances, and parametric uncertainties. The control system has a double loop in a cascade configuration, where the outer loop has an integral (I) action driven by the joint deflection error. In addition, the inner loop has a nonlinear proportional-integral-derivative (PID-type) structure. Hence, an I-PID-type controller is obtained. The design methodology is based on a linear change of coordinates of the joint deflection and motor errors that allows the conclusion of global asymptotic stability via Lyapunov theory and the Barbashin-Krasovskii theorem. Sufficient conditions are explicitly stated and given in the form of matrix inequalities. Real-time experiments on a two-degrees-of-freedom flexible joint manipulator confirm the viability of the proposed controller, which exhibits better performance than the other two control algorithms.